Descriptive profile of scapulothoracic position, strength and flexibility variables in adolescent elite tennis players - Cools, A. M.; Johansson, F. R.; Cambier, D. C.; Velde, A.V.; Palmans, T.; Witvrouw, E. E. (British Journal of Sports Medicine, 2010)
STUDY DESIGN: Descriptive study, cross-sectional design.